Education of a Future Human is the Key to Solving the Global Problems Facing Humanity - Olga Khrystenko (International Society of Philosophy and Cosmology, 2016)
The present research considers two Global problems of the humanity:intercivilizational contradictions and the pandemic of abortion as serious conflicts, the solution of which depends on the relevant public educational policies. The tension in the relationship between the Islamic World and the West, caused by the so-called "caricature scandal", encourages to understanding the conflict and the ways of its solution. There is also the problem of massive numbers of abortions in the world that requires a scientific analysis and relevant conclusions. The research revealed that both sides of intercivilizational conflicts are responsible for it. The freedom of speech as an ingredient of democracy cannot exist only for itself. It should be based on the human values, including respect for other nations, religions, cultures, as well as the protection of human life. The second part of the research concerns the pandemic of abortion. Based on the achievements of modern embryology, sociology and bioethics, four levels of this conflict were defined. The first level is a conflict concerning the life of the unborn child. The second one is a conflict concerning a mother. The third one is a conflict with the nation. The fourth one is a conflict with God. On these issues, the survey was conducted among the first year medical students at Ternopil State Medical University. It was also concluded that it would have been useful to present the model of state policy aimed to prevent conflictsbetween civilizations, aswellasthepandemicofabortiontothestudents. Thispolicy should include: information policy (promotion of the idea that human life is the highest value, and human relationships should be based on the principles of tolerance); education policy (education in today's youth of the culture of interpersonal relationships based on honesty, responsibility); social policy (creation of the material conditions for young families, single mothers); policy in the health sector (providing high quality medical services, maternal and child health); policy in the sphere of law (the adoption of laws that will protect the lives of unborn children).